Salisbury biochar did not affect the mobility or speciation of lead in kaolin in a short-term laboratory study. - Shen, Zhengtao; McMillan, Oliver; Jin, Fei; Al-Tabbaa, Abir (Elsevier BV, 2016)
Salisbury biochar (produced from British broadleaf hardwood) with two different particle sizes (≤2mm and ≤0.15mm) was applied on a kaolin with three different lead (Pb(2+)) contamination levels (50mg/kg, 300mg/kg and 1000mg/kg) at the dosage of 1% in w/w. The short-term impact of biochar on the mobility and speciation of Pb(2+) in the kaolin was investigated using attenuation periods of 1, 7 and 28 days. The leachability and extractability of Pb(2+) in carbonic acid leaching and EDTA extraction tests as well as the speciation of Pb(2+) in soils were not significantly affected by biochar treatment during all periods. The insignificant effects of biochar on Pb(2+) immobilisation were most likely attributed to the high adsorption capacity of Pb(2+) on the kaolin and biochar failed to competitively adsorb Pb(2+) against kaolin. The kaolin immobilised Pb(2+) primarily through cation exchange, which represents the readily bioavailable fractions of Pb(2+) in soils and may still pose environmental risks. This paper suggests the inefficiency of biochar treament on heavy-metal contaminated clay-rich soils. Therefore a laboratory treatablity study with respect to the soil type may be crucial when large-scale biochar applications in heavy-metal associated soil remediation are evaluated.